Auditor Competence in Digital-Based Government Organizations: Systematic Literature Review - Nurharjanti, Nashirotun Nisa (Jurnal Akuntansi dan Bisnis, 2024)
Technological innovations in the audit process can transform organizations and individuals. Government organizations have developed digital-based audit services. This research focuses on auditor competencies that can be used by government organizations in the digital era. This research explains how to research auditor competency in government organizations in the digitalization era, investigates the focus and criticism of the literature on auditor competency in government organizations in the digitalization era, and develops future research related to auditor competency in government organizations in the digitalization era . A structured literature review was conducted for governmentations in English regarding auditor competency in digitally based government organizations. The results reveal that the number of governmentations related to auditor competency in digital-based government organizations has experienced growth over the last ten years. However, the assessment of auditor competency indicators automatically does not imply all of the factors that influence an auditor's competency, because the assessment of auditor competency indicators can be influenced by organizational culture, and organizational and environmental factors. Guidance on competency becomes dynamic because accounting information continues to change accompanied by technological development. So, assessing auditor competency is an important component for improving audit quality. There is no evidence that states which competency is the most dominant, although information technology competency and problem solving skills or analysis and data literacy are competencies that are often studied by researchers. This research has limitations, namely that future research directions come from recent research. So, it is possible that the picture is still far from complete because no one yet knows the speed of technological evolution. This article focuses on aspects of auditor competency assessment that can be used by government organizations, which emphasize technological developments